Sistem Informasi Monitoring Kolektibilitas dan Manajemen Penagihan Piutang Koperasi Berbasis Web - Mochammad Guntur Ramadhan; Dani Yusuf; Dwi Budi Srisulistiowati (Journal of Informatic and Information Security, 2026)
This research was motivated by the conventional receivable management process at Koperasi Konsumen Serba Usaha Desa Bersinar. The use of basic spreadsheet software for payment recording led to limitations in the real-time monitoring of members' collectability status and the absence of an early warning system for late payments, which hampered the cooperative's cash flow. The objective of this study was to design and develop a web-based information system for collectability monitoring and debt collection management. The system development employed the Waterfall method and Model-View-Controller (MVC) architecture, utilizing PHP and MySQL. The novelty of this system lies in the implementation of an automated classification function for five levels of collectability status (Current, Special Mention, Substandard, Doubtful, and Loss) by utilizing conditional logic and date manipulation based on the calculation of days past due (DPD). The functional testing results using the Black Box Testing method indicated that all application features operated in accordance with user requirement specifications. The implementation of this system assisted the cooperative in automating receivable risk monitoring and provided a technological blueprint to prevent the risk of non-performing loans in similar institutions.